Dvikamienių lietuvių vyrų vardų kirčiavimas: pirmųjų dėmenų tvirtapradė priegaidė - Pakerys, Antanas (Baltistica, 2009)
ACCENTUATION OF LITHUANIAN COMPOUND MALE NAMES: THE ACUTE OF THE FIRST COMPONENTIn this paper, the main etymologies of the first components of Lithuanian compound male names are reviewed and the accentuation of these compounds is compared with the accentual properties of their base words, the modern surnames, and respective place names.The acute of the first stressed component of Lithuanian compound male names  is most often inherited from the corresponding common nouns, verbs, prepositions, etc. The acute diphthongs of the types aR, eR, iR, and uR usually correspond to the heterosyllabic sounds in stressed roots of non-proper words. The acute of the first component is almost always confirmed by the accentuation of compound surnames or the place names of anthroponomical origin.
Keywords: onomastika; akcentologija; dvikamieniai